Responses to Sensory Events in Daily Life in Children with Cerebral Palsy from a Parent Reported Perspective and in a Swedish Context - Annika Ericson; Åsa Bartonek; Kristina Tedroff; Cecilia Lidbeck (MDPI AG, 2023)
The motor disorders of cerebral palsy (CP) are often accompanied by sensory disturbances, but knowledge of their relationship to motor functioning is sparse. This study explored responses to sensory events in relation to spastic subtype and motor functioning in children with CP. Parents of 60 children with CP (unilateral: 18, bilateral: 42) with GMFCS levels I:29, II:13, III:15 and IV:3 of mean age 12.3 years (3.7 SD) participated. The parents (n = 55) rated their children´s responses with the norm-referenced questionnaire Child Sensory Profile-2© (CSP-2©), Swedish version, incorporating nine sections and four sensory processing patterns/quadrants, and replied (n = 57) to two additional questions. On the CSP-2©, thirty (55%) of the children were reported to have responses "much more than others" (>2 SD) in one or more of the sections and/or quadrants and 22 (40%) in the section of Body Position, overrepresented by the children with bilateral CP. The additional questions revealed that a greater proportion of children at GMFCS levels III-IV compared to level I frequently were requested to sit/stand up straight (14/17 versus 6/26, p < 0.001) and were sound sensitive at a younger age (14/17 versus 10/26, p = 0.005). The findings of this study highlight the sensory aspects of motor functioning in children with spastic CP.